KEPEMIMPINAN IDEAL DALAM AL-QUR’AN DAN ALKITAB: KAJIAN KOMPARATIF ATAS QS. ALI-IMRAN [3]: 59 DAN SURAT II TIMOTIUS 2 - Maula Sari (UIN Sunan Kalijaga Yogyakarta, 2020)
The purpose of this paper is to provide an explanation of the characteristics of leadership in the Islamic religion which refers to the Koran, and Christianity which refers to the gospel. The research method used will be qualitative and literature. Leadership especially in Indonesia has always been a hot topic in this modern era. So, in Islam and Christianity also discusses the concepts of leadership that have been discussed in the respective scriptures for the sake of the smoothness of a nation, then referring to the holy book itself. Based on the entire discussion in writing, it can be concluded that in Islam That ideal is a good temper and a gentle heart, forgiving and praying, and the common interest is decided together. Meanwhile, according to Christianity, the ideal leader is a guide, who can be trusted, who lives in holiness, who lives in consistency, and leaders who have courage and humility.